Family-State Mentality and Chinese Christian Studies - LI, Xiangping (Journal of Research for Christianity in China (JRCC), 2025)
This article is an online lecture paper. The article discusses the traditional and modern family-state mentality and Chinese Christian studies. First, it analyzes what is the family-state mentality. The family-state mentality refers to an ultimate emotional, ultimate personality mentality characterized by the Chinese divine archetype. Next, Locke's critique of patriarchal-kingly power is discussed; again, Bellah's comparative study on the Confucian-Jewish father-son relationship is sorted out. Finally, it analyzes the reverential habit and the familial mentality, pointing out that the familial mentality converts its special logic from familial power to specific individuals, souls, spirits, and emotions, so that not only the familial category of mentality contributes to the sanctity of individuals, but also to the ethics of individual sanctity and the equality and freedom of individual sanctity. This article argues that the family mentality transforms its special logic from the family power to the specific individual, soul, spirit, and emotion, so that the family-like mentality not only contributes to the sanctity of the individual, but also to the ethics of the individual sanctity and the equality and freedom of the individual sanctity.